2022
DOI: 10.1007/s10639-022-10950-8
|View full text |Cite
|
Sign up to set email alerts
|

Modelling online community constructs through interaction data: A learning analytics based Approach

Abstract: This study aims to use LMS log data to suggest a way to understand CoI constructs. Students' interactions in Moodle components were weighted for indicators of cognitive, teaching and social presences. Traces reflecting students' online interactions were obtained from the Moodle LMS and analyzed through learning analytics techniques. The data is examined with the Euclidean Distance Model, and Correspondence Analysis methods to evaluate the levels of interactions and presences. The results indicated that, cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…1 This finding is consistent with those obtained in the studies by Kumar et al 25 and Çakiroglu & Kahyar. 9 These studies found that studentcontent interaction has a significant effect and the strongest effect on student satisfaction. Among the student-faculty interactions (hypothesis 2), the student-messenger interaction (hypothesis 2-1) was accepted, but the student-zoom interaction (hypothesis 2-2) was rejected.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 This finding is consistent with those obtained in the studies by Kumar et al 25 and Çakiroglu & Kahyar. 9 These studies found that studentcontent interaction has a significant effect and the strongest effect on student satisfaction. Among the student-faculty interactions (hypothesis 2), the student-messenger interaction (hypothesis 2-1) was accepted, but the student-zoom interaction (hypothesis 2-2) was rejected.…”
Section: Resultsmentioning
confidence: 99%
“…Çakiroğlu & Kahyar 9 revealed the relationship between presence and interaction using the Euclidean distance model and correspondence analysis. According to the results of the study, cognitive presence is at the center of CoI framework, and the relationship with student-system (technology) interaction is more prominent than those with other interactions.…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Online communities have transformed the way individuals engage in learning, collaboration, and personal growth [14], [15]. These digital platforms create a sense of belonging, allowing members to connect, exchange experiences, and support each other [16].…”
Section: Mentorship Platforms and Online Communitiesmentioning
confidence: 99%
“…The chief aspects of online communities have peer support networks [9], knowledge sharing, collaborative learning, network opportunities. In online community-based learning, the members provide encouragement, advice, and moral support to one another [7] and exchanging ideas, best practices, and valuable insights under knowledge sharing attribute [14]. Interactive discussions, group projects, and peer-to-peer feedback comes under collaborative learning [12], [17].…”
Section: Mentorship Platforms and Online Communitiesmentioning
confidence: 99%